N-acetyltransferase 8, a positional candidate for blood pressure and renal regulation: resequencing, association and in silico study - Rosenberg Mai; Kelgo Piret; Veldre Gudrun; Org Elin; Kepp Katrin; Juhanson Peeter; Viigimaa Margus; Laan Maris (BMC, 2008)
Abstract Background Kidneys have an important function in blood pressure (BP) regulation and elevated BP may lead to kidney failure. Chr2p12-p13 region linked to BP traits in multiple studies harbours a potential candidate for BP and renal function, N-acetyltransferase 8 (NAT8) expressed in embryonic and adult kidney and associated with nephrotoxicity response. Methods/Results We report the first study exploring NAT8 as a potential candidate gene for blood pressure and kidney function. The resequencing (n = 42, random Estonian samples) identified 15 NAT8 polymorphisms, including 6 novel variants. The diversity of NAT8 5' upstream region (π/bp = 0.00320) exceeded up to 10 times the variation in the NAT8 genic region (π/bp = 0.00037) as well as the average variation (π/bp = 0.00040) for the promoters of 29 reference genes associated with hypertension. We suggest that a potential source for such high variation could be an active gene conversion process from NAT8B duplicate gene to NAT8. Similarly to NAT8, several reference genes with the most variable upstream regions have also duplicate copies. The NAT8 promoter SNPs were targeted with pilot quantitative association studies for blood pressure (n = 137, healthy unrelated individuals) and for the index of kidney function - estimated glomerular filtration rate (eGFR; n = 157 hypertensives with and without nephropathy). Minor alleles of these polymorphisms revealed a significant protective effect against elevated systolic BP as well as kidney failure in hypertension patients (p < 0.05; linear regression model, addictive effect). Conclusion The full resequencing and pilot association study of a novel positional candidate gene for blood pressure and renal function, human N-acetyltransferase 8, suggested a contribution of highly variable NAT8 promoter polymorphisms in determination of systolic blood pressure and eGFR. Based on in silico analysis, we raise the hypothesis that the alternative SNP alleles of the NAT8 upstream region may have differential effect on gene expression.